DEMOCRATIC CHALLENGES OF INDONESIA IN THE SOCIAL MEDIA ERA - Nunik Nurhayati; Rohmad Suryadi (Fakultas Hukum, Universitas Diponegoro, 2017)
The era of social media today bring significant change to democracy in Indonesia. Social media can to bring the expansion of the public space in cyberspace, citizens can directly deliver aspirations regarding the state policy. However, on the other side, social media vulnerable to abuse because of many the anonymous account, which acts as the buzzer political influence public perceptions and to get political support but is not elegant way. This shows, social media provides a challenge to democracy, including Indonesia as a third largest country that has access to the social media in the world's. Based on it’s the problems, this research aims to identify the impact of the social media on democratic life, and how the challenges of democracy in Indonesia ahead in the social media today.This Research using qualitative methods. Data collection through the study of literature. Then analyzed with a critical discourse analysis. The results of the study showed that the impact of social media in Indonesia has brought problems such as hoax, which is currently a serious concern of the government. Attempts were made through the campaign against hoax and make regulation, Information and Electronic Transactions Law (ITE Law), which aims to regulate the use of social media and to prevent hoaxes. The life of democracy in Indonesia receive significant challenges,but of the repressive laws against users of social media may actually weaken the democratic life in Indonesia.